Moderate hypothermia attenuates oxidative stress injuries in alveolar epithelial A549 cells. (1st August 2013) - Chiou, Shr-Yun; Lee, Yu-Sheng; Jeng, Mei-Jy; Tsao, Pei-Chen; Soong, Wen-Jue
ABSTRACT: Reactive oxygen species (ROS) are generally involved in lung inflammation and acute lung injury. We investigated the effects of hypothermia on ROS-induced cell damage in human alveolar type II cells. A549 cells were exposed to H2 O2 and cultured at different temperatures, namely, normthermia (37°C), mild hypothermia (34°C), or moderate hypothermia (32°C). Cell damage was measured using various assays. The biochemical studies demonstrated a significant increase in apoptosis and intracellular ROS at 32°C in uninjured A549 cells. After exposure to H2 O2, a marked decrease in cell viability (<50%) was demonstrated, and this was significantly ameliorated upon culture at 32°C. Significantly intracellular damage was found to affect the 24-hour H2 O2 -exposed cells in 37°C ( P < .05), including an increase in apoptosis and necrosis, intracellular ROS, caspase-3 activity, HMGB1 protein expression, and some alterations to the cell cycle. On hypothermic treatment, the 24-hour H2 O2 -induced caspase-3 activation was significantly suppressed in cells cultured at both 32°C and 34°C ( P < .05 versus 37°C). The cell cycle changes in 24-hour H2 O2 -exposed cells were significantly diminished when the cells were cultured in 32°C ( P < .05 versus 37°C). However, these intracellular alterations were not seen in 6-hour H2 O2 -exposed cells. We concluded that moderate hypothermia (32°C) of alveolar epithelial A549 cells seems to provide protection against H2 O2 -induced 24-hour oxidative stress by attenuating cell death and intracellular damage. However, moderate hypothermia might cause minor damage to uninjured cells, so the use of hypothermic treatment needs to be judiciously applied.